Associations between Sagittal, Transversal, and Vertical Planes with Dental Anomalies in Pretreatment Orthodontic Patients of Kosovo - Selmani, Mimoza; Bukleta, Manushaqe Selmani (European Journal of General Dentistry, 2025)
The objective of this study was to compare the different types of malocclusions in the sagittal, transverse, and vertical planes and to assess their association with dental anomalies such as hypodontia, ectopic eruption, and anterior and posterior crossbite.The sample population was selected from orthodontic specialty clinics in Pristina, Kosovo. The study was conducted by recruiting 617 patients; 377 (61%) were female and 240 (39%) were male. The following occlusal relationships (regarding Angle's classification) were assessed during the examination of study casts: molar and canine sagittal relationships and coincidence of incisal midlines. Malocclusion in the transverse plane, vertical plane, and anterior and posterior crowding in both jaws was examined.In the sagittal plane, the majority of both females (45.6%) and males (42.9%) belonged to class I. However, males had a higher proportion in class III (22.5) compared with females (16.4%). In the transversal plane, the upper midline was predominantly on the right side for both genders. For the lower midline, both genders showed almost a similar distribution. The vertical plane analysis indicated that deep bite is more common in males (31.7%) than females (30.2%). In contrast, females had a slightly higher occurrence of open bite (15.9%) compared with males (11.7%). Regarding dental anomalies, hypodontia affected a higher percentage of males (13.8%) compared with females (12.2%).In the sagittal plane, class I is common in both genders, while the males show higher class III prevalence. In the transversal plane, upper midline deviation to the right is slightly more frequent in females. Regarding vertical plane, deep bite is somewhat more prevalent in males, whereas open bite is more common in females.
Keywords: malocclusion; dental anomalies; crowding; crossbite; sagittal plane; transversal plane